SYNTHESIS AND CHARACTERIZATION OF IRON OXIDE NANOLEAF BY THERMAL OXIDATION - Ismail, Syahriza; Abu Bakar, Noor Farah Iddayu; Mustafa, Zaleha; Omar, Noor Irinah; Ibrahim, Siti Aida (2023)
In this work, a simple method for the efficient and rapid synthesis of onedimensional hematite (α-Fe2O3) nanostructures is proposed based on a thermal oxidation approach. This technique is to create iron oxide nanoleaf on the iron (Fe) substrate. The oxidation was done at three different temperatures (200-600 oC) by oxidizing the Fe foils in a chamber furnace. The low temperature thermal oxidation at 400 oC for 2 h resulted in the formation of hematite iron oxide with good nanoleaf coverage on the foil surface. The obtained nanostructures physical and structural characteristics were characterize using XRD, and Raman spectroscopy. While their morphological characteristics were observed using the FESEM. It was discovered that when the oxidation period lengthened, the peak intensities in relation to the hematite increased. The duration of heating has a substantial impact on the development and ultimate morphology of hematite. The creation of this nanostructured formation's growth phenomenon was subsequently explained by a surface diffusion mechanism. According to the X-ray diffraction results, the iron oxide nanoleaf was Fe3O4 and α -Fe2O3 after the oxidation. The dimension of the nanoleaf was found to be 20-60 nm and lengths up to 1 µm. These dimensions are dependent on the oxidation temperature. The activation energy on the crystallographic plane and grain boundary has an impact on how nanostructures grow during oxidation.